2019
DOI: 10.1007/s10530-019-02069-8
|View full text |Cite
|
Sign up to set email alerts
|

Single zooids, multiple loci: independent colonisations revealed by population genomics of a global invader

Abstract: Assessing genomic diversity and population structure of non-indigenous species is crucial to develop adequate management strategies. However, in species with scarce material for DNA extraction, applying genomic techniques can be a difficult task. Here we set a protocol for small DNA samples combining whole genome amplification (WGA) and genotyping-by-sequencing (GBS). This protocol was applied to the worldwide invasive colonial ascidian Didemnum vexillum using a single zooid per colony. WGA-GBS performance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 114 publications
0
39
0
Order By: Relevance
“…A total of 65 colonies of D. vexillum from 12 locations spanning the native (NW Pacific) and the known introduced distribution of the species were sampled during 2015 and 2016 in marinas and artificial substrates (Table 1 and Figure 1). Sequences of the specimens showed that five colonies were D. vexillum clade B from Sugashima (Japan), whereas the remaining 60 colonies were D. vexillum clade A from different temperate regions of the world (Casso et al, 2019b). Thus, only in one of the two populations (Sugashima and Aomori) corresponding to the native range of the species did we find the two described mitochondrial clades in sympatry.…”
Section: Samplingmentioning
confidence: 78%
See 4 more Smart Citations
“…A total of 65 colonies of D. vexillum from 12 locations spanning the native (NW Pacific) and the known introduced distribution of the species were sampled during 2015 and 2016 in marinas and artificial substrates (Table 1 and Figure 1). Sequences of the specimens showed that five colonies were D. vexillum clade B from Sugashima (Japan), whereas the remaining 60 colonies were D. vexillum clade A from different temperate regions of the world (Casso et al, 2019b). Thus, only in one of the two populations (Sugashima and Aomori) corresponding to the native range of the species did we find the two described mitochondrial clades in sympatry.…”
Section: Samplingmentioning
confidence: 78%
“…All 70 colonies were collected in marinas and other artificial substrates, at least 2 m apart from each other to avoid pseudoreplication (Smith et al, 2012), and preserved at −20 • C in 96% ethanol. Samples were coded by geographic region as defined in previous studies (Stefaniak et al, 2012;Casso et al, 2019b). Clade A introduced samples were assigned to the previously defined genetic groups (Casso et al, 2019b): Europe (EUR), West North America (WNA), and New Zealand plus East North America (NZ-ENA).…”
Section: Samplingmentioning
confidence: 99%
See 3 more Smart Citations